Correlation of Nogo A release with glia scar formation in spinal cord injury (Research, Society and Development, 2021)
Several axonal growth inhibitors have already been identified following spinal cord injury, the most known being myelin-derived proteins, such as Nogo-A. The present study aimed to correlate the formation of glial scar with the beginning of growth inhibitor, Nogo-A, release in rats previously submitted to compressive spinal cord injury. For this, 12 male and female Wistar rats (250 ± 50g) were divided into 3 groups of 4 animals each, according to the animals' euthanasia time after spinal cord injury (G3 - three days; G5 - five days; G7 - seven days). Spinal cord injuries were induced by means of dorsal laminectomy of the T10 vertebra and epidural compression. Histopathological evaluation and immunoreactivity of the Nogo-A axonal growth inhibitor were performed. It was observed that there was the release of the axonal inhibitor Nogo-A after 24h after the occurrence of spinal cord injury, and that the glial scar must be maintained, in this time interval, in order to guarantee the rebalancing of the post-trauma environment. Thus, it is suggested that the glial scar should be maintained in the acute phase of the lesion, guaranteeing its numerous benefits for the rebalancing of the post-injured environment and, after 24 hours, when the release of the studied axonal growth inhibitor begins, it should be removed.